SPIRITUALITY AS THE FOUNDATION OF HUMAN AND SOCIETAL CULTURE - Jomoliddi Togaymurodov; Sumbula Sharipova (Western European Studies, 2024)
This article discusses the formation of human and societal culture, emphasizing that spirituality isthe foundation of human and societal civilization. Today, the growing interest in mass culture and European culture among the youth is examined, highlighting the importance of shaping our cultural mentality.
Keywords: Spirituality; society; human culture; education